Дослідження властивостей кремнієрганічного адсорбенту ''КРЕОСОРБ'' - Бойченко, С.В.; Швець, О.В.; Черненко, Ж.В.; Черняк, Л.М. (Видавничий дім "Академперіодика" НАН України, 2007)
We describe the results of researches of synthesized organosilicon sorbents. The sorption properties of a perspective sorbent with the completely hydrophobic surface (symbolic title ''KREOSORB'') considerably exceed those of the available silica gels. This allows us to predict its successful use in solving the actual ecological and power-supply problems.